2015
DOI: 10.1038/npp.2014.335
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Serotonergic Function in the Orbitofrontal Cortex and Dorsal Raphé Nucleus Predict Individual Variation in Spatial-Discrimination Serial Reversal Learning

Abstract: Dysfunction of the orbitofrontal cortex (OFC) impairs the ability of individuals to flexibly adapt behavior to changing stimulus-reward (S-R) contingencies. Impaired flexibility also results from interventions that alter serotonin (5-HT) and dopamine (DA) transmission in the OFC and dorsomedial striatum (DMS). However, it is unclear whether similar mechanisms underpin naturally occurring variations in behavioral flexibility. In the present study, we used a spatial-discrimination serial reversal procedure to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 66 publications
4
66
0
Order By: Relevance
“…Errors were considered perseverative in nature if in a window of 10 trials, 7 incorrect responses were made. The number of perseverative errors made during the three reversals was used to rank the animals, consistent with (Barlow et al 2015). Based on this ranking, three groups were formed that included highly perseverative ( n  = 11), mid-range ( n  = 20), and low-perseverative animals ( n  = 11).…”
Section: Methodsmentioning
confidence: 99%
“…Errors were considered perseverative in nature if in a window of 10 trials, 7 incorrect responses were made. The number of perseverative errors made during the three reversals was used to rank the animals, consistent with (Barlow et al 2015). Based on this ranking, three groups were formed that included highly perseverative ( n  = 11), mid-range ( n  = 20), and low-perseverative animals ( n  = 11).…”
Section: Methodsmentioning
confidence: 99%
“…OFC 5HT depletion studies in marmosets and rats have indicated impairments in serial visual reversal learning [45, 97, 98], detour-reaching task [46] as well as attentional set-shifting task [99]. Likewise, 5HT markers in the rodent OFC have been shown to correlate with performances on a spatial reversal learning task while its reuptake inhibitor, citalopram was shown to improve performance [100]. In contrast, OFC specific administration of a 5-HT 2C antagonist significantly enhanced performance on different reversal learning based tasks [101103].…”
Section: Discussionmentioning
confidence: 99%
“…For example, rats systemically treated with para-chloroamphetamine (PCA) or parachlorophenylalanine (PCPA), both of which produce significant depletion of brain serotonin, showed impaired stimulus-reward, discrimination and reversal learning (Masaki et al, 2006, Izquierdo et al, 2012). However, serotonin and serotonin transporter levels in the rodent OFC predict individual variation in reversal learning performance, suggesting a more circumscribed role for the transmitter (Stolyarova et al, 2014, Barlow et al, 2015). A study in vervet monkeys by Groman and colleagues also reported that serotonin levels in ventrolateral PFC/Area 47 correlated with reversal learning performance (Groman et al, 2013).…”
Section: Neurochemical Modulation Of Reversalmentioning
confidence: 99%